PENERAPAN MODEL PEMBELAJARAN GALLERY ACCOUNTING DAPAT MENINGKATKAN HASIL BELAJAR SIKLUS AKUNTANSI PERUSAHAAN JASA BAGI SISWA KELAS XI IPS-5 SMA NEGERI 4 PEKANBARU PADA SEMESTER 2 TAHUN PELAJARAN 2015/2016 - Sakdiah Sakdiah (UIR PRESS, 2017)
The purpose of this study was to determine the learning outcomes Accounting Services Company Accounting Cycle material through the application of learning models Gallery Accounting.Results of learning materials Accounting Cycle Accounting Services Company is expected to increase, so the basic competencies to be achieved in the learning process can be mastered by the student to the fullest.Where the research was conducted in SMA Negeri 4 Pekanbaru, the Adi Sucipto No. 67 Pekanbaru.Subjects in this study were students of class XI IPS-5 school year 2015/2016 totaling 34 students consisting of 20 girls and 14 boys.The research method using action research methods class.Much of the action three times in three cycles.Each cycle consists of four stages covering action planning, action, observation results of actions, and reflecting the results of the action.The results showed that the condition pratindakan average value obtained by 76 students, the first cycle = 84, the average value of the second cycle = 86, and the third cycle = 89, then from the condition pratindakan compared to the third cycle increased by 13.This indicates that the use of models Gallery Accounting learning can improve learning outcomes in particular Accounting Services Company Accounting Cycle material.Based on the conclusions of this study need to be tested on other subjects.Need to develop models of learning Gallery Accounting Accounting on different materials.Learning need to be designed using the Gallery Accounting with different learning models.